Antithrombotics in Complex Percutaneous Coronary Interventions: Type and Duration of Treatment - Despoina-Rafailia Benetou (Radcliffe Medical Media, 2021)
Patients undergoing complex percutaneous coronary intervention (PCI) are at an increased risk of atherothrombotic complications. Although dual antiplatelet therapy is the mainstay of treatment for patients undergoing PCI with stent implantation, deciding its type and duration in complex PCI patients has long been considered a challenge for clinicians. This is because the beneficial effects of prolonged treatment and/or more potent antiplatelet agents’ use in preventing ischemic events are hindered by a concomitant increase in bleeding complications. The aim of this review is to highlight current evidence regarding the optimal antithrombotic therapy regimens used in complex PCI patients, focusing on the evaluation of both safety and efficacy outcomes as well as addressing future perspectives.